Can Digital Technologies Play a Role in Improving Children's Learning Outcomes in India?. (January 2018) - Banerjee, Sashwati; Chakravarty, Sujoy; Joshi, Ira; Pillai, Siddharth
Abstract: In this study, we explore the effects of an educational intervention in the form of digital games targeted towards improving the learning outcomes in mathematics and Hindi language among first, second and third graders in four government schools in southern New Delhi. In addition to administering these games in the classroom, we randomly recruited 40 households from a low-income community, where children play the games as an extra-curricular activity. We measure the improvement in aptitude in math and Hindi pre- and post-intervention, using various demographic controls and find that the community intervention had some impact in boosting aptitude. In contrast, the school intervention did not show the desired results though it did register some improvement in children's knowledge. Using qualitative observation coupled with the quantitative assessment of impact, we attempt to deconstruct the various infrastructural challenges and sampling issues posed in our school intervention, and identify key features that need to be adhered to for future researchers who may want to assess the impact of educational interventions on young children from underprivileged backgrounds in India.